(untitled) (Global Journal of Management and Business Research, 2020)
The government of Sierra Leone in 2017 indicated that increasing borrowings along with tax measures are the only options available to drive the economy out of recession and sustain growth for now Smith (2017). Debt can be defined as any money owed by an individual, firm or government to a lender. Luke (2017) defined debt as a contractual obligation of owing or accumulated borrowing with a promise to payback at a future date. A developing country like Sierra Leone, wanting to mobilize capital resources to foster economic growth may at one-point resort to borrowing. But why do countries borrow? Countries borrow because of their inability to generate enough savings which could be used for investment. According to Johnson (2018) the amount of capital available in most developing countries treasury is grossly inadequate to meet their economic growth needs due to low productivity, low savings and high consumption pattern.